ANALISIS PENERAPAN PERMAINAN TRADISIONAL ENGKLEK PADA ANAK USIA DINI - Maulina, Iin; Herawati, Herawati; Wihartati, Irma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the condition of the traditional game Engklek on Sentosa Street, RT.10 RW.04, Kapuas Hulu Regency, with a focus on early childhood (5-6 years old). This research is descriptive in nature, utilizing data collection techniques such as observation, interviews, and documentation. The results of the research indicate that the Engklek game has positive potential with adequate playing space, but it requires improvements in physical aspects and supporting facilities. The community's awareness of preserving this game is relatively good, but there is a need for an increased understanding of cultural values. Supporting factors involve community support, educational institutions, and the government, but collaboration needs to be enhanced. The implementation of Engklek in early childhood provides benefits in the development of motor skills, social skills, and cultural values. Therefore, collaborative efforts are needed to raise awareness and provide facilities that support the traditional game to remain relevant for children.